Sectoral partnerships - (:unkn) unknown (Office for Official Publications of the European Communities, 2009)
"This publication draws on the general principles of sectoral partnership for lifelong learning. Looking at some of the challenges different sectors face, such as international competition, free trade and technological advancement it asks how changes and challenges can be translated into human resource priorities and strategies. Guided by practical examples from Europe, it considers how priorities and strategies can become qualifications and focuses on the practicalities of establishing sectoral partnerships. It discusses how sectoral partnerships can be funded, including training funds, individual contributions and the role of collective bargaining. The international perspective and the European developments related to the Lisbon and Copenhagen processes are highlighted, examining areas where closer European integration is desired and how this can be achieved. Finally, it considers the resources available to support the development of sectoral partnerships in Europe." (Herausgeber, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 2.4 Kooperation; S 3.5.4 Sozialpartner; S 4.1 Finanzierungsquellen; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Lebenslanges Lernen; Bildungsnetzwerk; Regionales Netzwerk; Sozialpartner; Bildungsfinanzierung; Sektoransatz; Nationaler Qualifikationsrahmen; Europäischer Qualifikationsrahmen; Europa